VARIABILITY, LANGUAGE CHANGE, AND THE HISTORY OF ENGLISH - Milroy, James (International Journal of English Studies, 2009)
In historical language scholarship, it has been usual to assume that The transmission of language from generation to generation is itself a linguistic, rather than a social, process, and that the focus should be on uniform language states. Here it is argued that transmission is necessarily social and that the history of a language is necessarily a history of variation. Firts, it is shown that the history of British Received Pronunciation is not one of direct descent from a single uniform ancestral variety. It is then demonstrated that pre-vocalic [h] and [hw] in English have a long history as variables and that loss of [h] in these combinations is not a recent event. Finally, it is suggested that closely similar variants of certain variables, such as [w] for (wh), have most probably recurred independently at various points in history and that we therefore need to review the methods used for dating sound changes.